Cell selective chitosan microparticles as injectable cell carriers for tissue regeneration. (March 2015) - Custódio, C.A.; Cerqueira, M.T.; Marques, A.P.; Reis, R.L.; Mano, J.F.
Abstract: The detection, isolation and sorting of cells holds an important role in cell therapy and regenerative medicine. Also, injectable systems have been explored for tissue regeneration in vivo, because it allows repairing complex shaped tissue defects through minimally invasive surgical procedures. Here we report the development of chitosan microparticles with a size of 115.8 μm able to capture and expand a specific cell type that can also be regarded as an injectable biomaterial. Monoclonal antibodies against cell surface antigens specific to endothelial cells and stem cells were immobilized on the surface of the microparticles. Experimental results showed that particles bioconjugated with specific antibodies provide suitable surfaces to capture a target cell type and subsequent expansion of the captured cells. Primarily designed for an application in tissue engineering, three main challenges are accomplished with the herein presented microparticles: separation, scale-up expansion of specific cell type and successful use as an injectable system to form small tissue constructs in situ .